Collaborative Control of Mobile Manipulator Robots through the Hardware in the Loop Technique. - Santo Guanoluisa, Luis Fernando (2021)
This article aims at designing and implementing the "Hardware in the Loop" (HIL) technique, to evaluate the Collaborative control algorithm of two mobile manipulator robots to carry out tasks of movement and manipulation of objects in an industrial environment. The developed control structure is made up of a centralized control algorithm, developed in Matlab mathematical software, which is linked to the HIL system, which contains both the kinematic model and the dynamic model of each robotic system programmed on the Raspberry Pi. To analyze the optimal functioning of the proposed control algorithm, an immersive virtual reality scenario is designed and implemented using the UNITY3D graphic engine, which facilitates interaction with the user.